PRO DAN KONTRA RANCANGAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG TENTANG SANKSI KEBIRI BAGI PELAKU PEDOFILIA DARI SUDUT PANDANG HAK ASASI MANUSIA - Norita Norita (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTPedophilia is an abnormal behavior and personality which tend to do sexual relationship with children.  There are many sexual abuse and criminal to children arouse anxiety to parent as well as community and country, so Indonesia currently can be categorized as face serious emergency situation relate to children sexual harassment criminality.  Punishment proposal for emasculated to criminal of pedophilia is consider could reduce and even prevent criminal act of sexual to children. However, there are pro and contra to this government regulation proposal which make Government should be aware and cautious to take decision. Especially if emasculated is against Human Rights issue.This research is conducted used normatif yuridis method with collect some books, Regulation and  professional to know various inputs as consideration from many communities and stakeholders toward Government Regulation proposal about emasculate from Human Right perspective. Research data source come from Regulation Act to Children Protection, Regulation Act on Human Rights, Criminal Act, Books, Journal, electronic media, print media as well as interviews.Results of researched by LPAI within years 2010-2014 from 21.689.797 cases, 58% are sexual criminal cases. From KPAI within years 2010-2014 from 22 millions cases, 42% are sexual criminal cases. From KPAID Samarinda in 2015 is 137 cases sexual abuse and criminal to children. These showed that sexual criminal to children are very high therefore it need sever punishment compare to previous punishment which regulated within Criminal Act Law or KUHP and State Law No. 35 Year 2014 about Children Protection. Severe punishment is needed to regulate in order to reduce and protection from sexual criminal action toward children without causing pro and contra within community and if it is against Human Right issue. Key Words: Pro and Contra,  Government Regulation,Emasculated, Pedofilia and Human Rights.